The Factors That Influence Purchasing Decisions Through Purchasing Interest As An Intervening Variable: The Factors That Influence Purchasing Decisions Through Purchasing Interest As An Intervening Variable - Pujianti, Kharisma; Ervina Indiworo, Rr Hawik; P, Ratih Hesty Utami (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this research is to determine the influence of brand image, word of mouth, testimonials, purchasing interest on purchasing decisions for Ms Glow products. To determine the influence of brand image, word of mouth, and testimonials on purchasing decisions for Ms Glow products with purchase interest as an intervening variable. The population in this study were consumers who purchased local skincare products, Ms Glow, in Rembang Regency. The sample in this research was Ms Glow users in Rembang Regency. So the number of respondents was rounded up to 100 people. So there were 100 respondents involved in this research.. This study uses primary data with the data analysis technique in this research uses SEM-PLS analysis. The results of this research state that Brand Image has no influence on Purchasing Decisions, Word of Mouth has a significant influence on Purchasing Decisions, Consumer Testimonials have no influence on Purchasing Decisions, Brand Image has no influence on Purchasing Decisions on Ms Glow Products which are partially mediated by Purchase Interest, Word of Mouth has no effect on purchasing decisions on Ms Glow products which are partially mediated by purchase interest, consumer testimonials have no effect on purchasing decisions on Ms Glow products which are partially mediated by purchase interest, purchase interest has no effect on purchasing decisions on Ms Glow products.